The Relationship Between Personal Hygiene and Incidence of Helminthiasis in Elementary School Students in Indonesia - Adnindya Krismahardi; Metriana Metriana (Jurnal Kesehatan Manarang, 2023)
Helminthiasis is an infectious disease caused by parasites in the form of worms that are usually transmitted through contaminated soil. Several things can be risk factors for disability in children. Risk factors for helminthiasis include Not washing hands with soap before eating; Not using footwear when going out of the house; Washing hands without soap after defecation; Frequent nail-biting; Playing on the dirty ground; Paying less attention to the food consumed. The purpose of this study was to determine the relationship between personal hygiene which consists of hand washing behavior, using footwear, and the habit of cleaning nails to the incidence of worms in elementary school students in Indonesia. This study used a meta-analysis method with secondary data obtained on the Google Scholar online database portal. Research articles obtained from Google Scholar and have gone through a selection process with inclusion criteria will enter the meta-analysis stage using JASP software. Based on the results of the meta-analysis, the personal hygiene variable was obtained which became the highest risk factor, namely handwashing behavior with a pooled PR value of 2,944 and 95% CI of 0.696-1,465, followed by variables of behavior using footwear with a pooled PR value of 2,351 and 95% CI of 0.326-1,384 and the smallest risk factor, namely nail cleaning behavior with a pooled PR value of 2,284 and 95% CI of 0.263-1,389. The sensitivity test results have variations with an increase in the pooled PR value from the fixed effect model to the random effect model as well as the widening of the Confident Interval value. In this study, it can be concluded that the behavioral variables of washing hands, using footwear, and cleaning nails can increase the risk of helminthiasis. Prevention efforts need to be carried out by educating children and parents to improve the personal hygiene of the child. Supervision efforts from parents are also needed to minimize the risk factor of helminthiasis in children.